Human sexuality: truth and significance. A guide for parents - Di Pietro, Maria Luisa (Medicina e Morale, 1996)
p>The article comments on the Pontifical Council for the Family (PCF)'s document on "The truth and meaning of human sexuality", which rather than a treaty on moral theology or on psychology, intends to be above all a moment of education for parents. The author then deals with the two main points of the pontifical document: the anthropology referred to and the methodological indications. Regarding the first point, the fundamental reference is the person in his totality of spirit and body. And sexuality is seen both as a way of being, and as a relationship dimension. It is therefore a sign of reciprocity and of the complementary aspect of the relationship, and as such it is naturally structured towards openess and giving to the other person. Regarding the methodological indications, the PCF's document supports the opportunities of educating the person with respect to sexual differences and to life in the sense of an education in the responsible management of freedom. This should be able to take place within the family, which is the first place of education, and should be carried out by the parents, who can be helped, in a subsidiary and subordinate way, by suitable educational organizations. The article concludes with the indications that the PCF's document provides on educative modalities: 1. informing by educating and educating by informing, according to the criteria of truth, making adequate and individualization, progressiveness, timeliness, of the decency and of the respect for the child; 2. the diversification according to the period of development and the vocation of the individual; 3. dealing with demanding situations like homosexuality and the prevention of sexually transmitted diseases in educational terms.